2012
DOI: 10.3390/ijerph10010047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Nanoparticles on Tobacco BY-2 Cell Suspension Culture

Abstract: Nanomaterials are structures whose exceptionality is based on their large surface, which is closely connected with reactivity and modification possibilities. Due to these properties nanomaterials are used in textile industry (antibacterial textiles with silver nanoparticles), electronics (high-resolution imaging, logical circuits on the molecular level) and medicine. Medicine represents one of the most important fields of application of nanomaterials. They are investigated in connection with targeted therapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 95 publications
(104 reference statements)
0
21
0
Order By: Relevance
“…Despite the great potential of iron nanoparticles to be used for different industrial and medical applications, data about their toxicity are still scarce [30]. Bearing in mind that in vitro tests represent a first step of biomedical application investigation [31], we have studied the toxicity of the obtained nanoparticles on HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the great potential of iron nanoparticles to be used for different industrial and medical applications, data about their toxicity are still scarce [30]. Bearing in mind that in vitro tests represent a first step of biomedical application investigation [31], we have studied the toxicity of the obtained nanoparticles on HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…For example, carbon nanotubes, gold (Au) nano-rods and titanium dioxide (TiO 2 ) NPs could enhance seed germination, root elongation as well as seedling growth (Khodakovskaya et al, 2009;Mondal et al, 2011;Servin et al, 2012;Wan et al, 2014;Yan et al, 2013). In contrast, other studies have reported that NPs, such as TiO 2 , cerium oxide (CeO 2 ), zinc oxide (ZnO), g-Fe 2 O 3 , could also cause damage in plants, including decreases in photosynthesis efficiency (Lei et al, 2007;Ze et al, 2011), chlorophyll degradation, total protein reduction (Krystofova et al, 2013;Zhao et al, 2013), as well as micro and macro-nutrient displacement Zhao et al, 2014a). Oxidative stresses caused by NPs could activate defense mechanisms to counteract nanotoxicity in plants ( Morales et al, 2013;Rico et al, 2013;Servin et al, 2013).…”
Section: Introductionmentioning
confidence: 91%
“…lanatus) and changed also the activities of SOD, POD, and CAT enzymes. The effects of nanoparticles of magnetite (γ-Fe 2 O 3 ) 24 nm in size and modified nanoparticles (Fe 2 O 3 -NH 2 , Fe 2 O 3 -OH) were studied in a tobacco BY-2 cell suspension culture (Krystofova et al 2013), specifically the effect on the growth and biochemical parameters of cells. γ-Fe 2 O 3 had no effect on cell growth and viability, but modified nanoparticles (Fe 2 O 3 -NH 2 , Fe 2 O 3 -OH) decreased the growth of cells; applied at 1 ng/ml, cell viability was reduced by 62.5 and 75 %, respectively, and by 45 and 60 %, respectively, when applied at 100 ng/ml.…”
Section: Explanation Based On Oriented Movements Of Substancesmentioning
confidence: 99%